2018
DOI: 10.1007/s00299-018-2326-1
|View full text |Cite
|
Sign up to set email alerts
|

Thidiazuron-induced abnormalities in plant tissue cultures

Abstract: Thidiazuron (TDZ) is a proven effective and potent synthetic plant growth regulator for organogenic, regeneration, and developmental pathways, including axillary and adventitious shoot proliferation, somatic embryogenesis, and in vitro flowering. TDZ has facilitated the establishment of in vitro cultures for several plant species, especially woody and recalcitrant plants, which has enabled their genetic transformation and improvement. Despite the effectiveness and advantages of using TDZ, several drawbacks are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
64
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 122 publications
10
64
1
2
Order By: Relevance
“…Meanwhile, TDZ-treated Philodendron 'Imperial Red' and 'Imperial Rainbow' explants were reported to form numerous leaf-like structures (Chen et al, 2012). Dewir et al (2018) suggested that TDZ-induced abnormalities and inhibition of shoot proliferation are due to overdose or continuous exposure for a long duration until organogenesis. BAP was more effective for inducing the shoot multiplication of lacy tree philodendron than the other cytokinins, as previously reported for other Philodendron species (Gangopadhyay et al, 2004;Han and Park, 2008; Jambor-Benczur and Marta-Riffer, 1990; Sreekumar et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, TDZ-treated Philodendron 'Imperial Red' and 'Imperial Rainbow' explants were reported to form numerous leaf-like structures (Chen et al, 2012). Dewir et al (2018) suggested that TDZ-induced abnormalities and inhibition of shoot proliferation are due to overdose or continuous exposure for a long duration until organogenesis. BAP was more effective for inducing the shoot multiplication of lacy tree philodendron than the other cytokinins, as previously reported for other Philodendron species (Gangopadhyay et al, 2004;Han and Park, 2008; Jambor-Benczur and Marta-Riffer, 1990; Sreekumar et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…1e). This fortified the existence of TDZ-induced abnormalities in tissue culture 27 . Our results show that new shoots could not develop in the presence of 2,4-D.…”
Section: Discussionmentioning
confidence: 96%
“…This was followed by Rio (7.2% of regenerating explants using the WU protocol), and Pink Kafir (23.7% of regenerating explants using the WU protocol), thus illustrating the high susceptibility of Pink Kafir to mutagenesis during in vitro development. This impact of genotype on albino regeneration has been noted during other in vitro regeneration studies (Ayed et al 2010; Khatun et al 2010; Park et al 2013), as has the impact of the in vitro protocol used (Khatun et al 2010; Park et al 2013; Sriskandarajah et al 2015; Dewir et al 2018).…”
Section: Discussionmentioning
confidence: 56%
“…As explants cultured using both protocols were incubated in the same types of culture vessels and the same tissue culture chamber, our evidence of the WU protocol being more promotive of albino regeneration suggested that medium composition played a role in this response. Previous studies have shown that inclusion of casein hydrolysate reduced albinism during in vitro regeneration (Sriskandarajah et al 2015), while the use of maltose as a carbohydrate source (Park et al 2013), TDZ as a cytokinin source (Dewir et al 2018) and copper supplements (Makowska et al 2017) promoted albinism. While the WU protocol was more supportive of overall plantlet regeneration than LG, this protocol contained almost 8-fold higher levels of copper sulfate in both CIM and RM formulations, as well as the use of maltose in CIM, and TDZ in RM.…”
Section: Discussionmentioning
confidence: 99%